The Surgical Approach for Adenomyosis in Nulligravid Women: A Case Report - Marlina Jaya Diputri; Prastika Candra Triastuti; Edy Priyanto (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Adenomyosis is a benign uterine condition characterized by endometrial tissue invasion into the myometrium. This often leading to chronic pelvic pain, dysmenorrhea, and infertility. A meta-analysis in 2025 reported prevalence ranging from 5.9% to 46.0%, with a mean of 20.7%. The Osada triple-flap technique was developed to remove adenomyotic tissue while preserving uterine function, serving as an alternative to total hysterectomy. However, intraoperative findings may require surgical adjustment.Case Report: A 32-year-old woman presented with severe abnormal uterine bleeding. Married for 11 years without children, she had a history of recurrent bleeding, multiple hospitalizations, blood transfusions, and myomectomy. Ultrasound showed an enlarged, globular, and heterogenous uterus with asymmetrical thickening. An exploratory laparotomy was performed with the intention of using the Osada technique, but, due to deep cul-de-sac adhesions and suspected malignancy, the surgery proceeded to total abdominal hysterectomy.Conclusions: Adenomyosis significantlyaffects fertility and uterus-preserving techniques like the Osada method may benefit selected patients. However, in cases with extensive adhesions, distorted anatomy, or suspected malignancy, hysterectomy remains the safest and most definitive treatment. AbstrakPendahuluan: Adenomiosis adalah kelainan jinak pada uterus akibat invasi endometrium ke miometrium. Kondisi ini sering menimbulkan nyeri panggul, dismenore, dan infertilitas. Meta-analisis tahun 2025 melaporkan bahwa prevalensi 5,9% hingga 46,0% (rata-rata 20,7%). Teknik Osada triple-flap dikembangkan untuk mengangkat jaringan adenomyosis sambil mempertahankan fungsi uterus, sebagai alternatif histerektomi total. Namun, temuan intra-operatif dapat mengubah rencana tindakan. Laporan Kasus: Perempuan 32 tahun datang dengan perdarahan uterus abnormal berat. Menikah 11 tahun tanpa anak, riwayat perdarahan berulang, beberapa kali rawat inap, transfusi darah, dan miomektomi. Ultrasonografi menunjukkan uterus membesar dan heterogen. Laparatomi eksplorasi direncanakan dengan teknik Osada (triple-flap), namun karena adanya adhesi dalam dan kecurigaan keganasan, dilakukan histerektomi total. Kesimpulan: Adenomiosis dapat mengganggu kesuburan. Metode preservasi uterus seperti metode Osada bermanfaat pada kasus terpilih, tetapi histerektomi total tetap menjadi pilihan paling aman dan efektif pada kasus kompleks dengan adhesi dan kecurigaan keganasan.